The effects of eccentric training on lower limb flexibility: a systematic review - O'Sullivan, K.; McAuliffe, S.; DeBurca, N. (British Journal of Sports Medicine, 2012)
Background - Reduced flexibility has been documented in athletes with lower limb injury, however, stretching has limited evidence of effectiveness in preventing injury or reducing the risk of recurrence. In contrast, it has been proposed that eccentric training can improve strength and reduce the risk of injury, and facilitate increased muscle flexibility via sarcomerogenesis. Objectives - This systematic review was undertaken to examine the evidence that eccentric training has demonstrated effectiveness as a means of improving lower limb flexibility. Study appraisal and synthesis methods - Six electronic databases were systematically searched by two independent reviewers to identify randomised clinical trials comparing the effectiveness of eccentric training to either a different intervention, or a no-intervention control group. Studies evaluating flexibility using both joint range of motion (ROM) and muscle fascicle length (FL) were included. Six studies met the inclusion/exclusion criteria, and were appraised using the PEDro scale. Differences in the muscles studied, and the outcome measures used, did not allow for pooled analysis. Results - There was consistent, strong evidence from all six trials in three different muscle groups that eccentric training can improve lower limb flexibility, as assessed using either joint ROM or muscle FL. Conclusion - The results support the hypothesis that eccentric training is an effective method of increasing lower limb flexibility. Further research is required to compare the increased flexibility obtained after eccentric training to that obtained with static stretching and other exercise interventions.